Gender disparities in patients undergoing extracorporeal cardiopulmonary resuscitation - Springer, A.; Dreher, A.; Reimers, J.; Kaiser, L.; Bahlmann, E.; van der Schalk, H.; Wohlmuth, P.; Gessler, N.; Hassan, K.; Wietz, J.; Bein, B.; Spangenberg, T.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction The use of venoarterial extracorporeal membrane oxygenation (VA-ECMO) in extracorporeal cardiopulmonary resuscitation (eCPR) has emerged as a treatment option for selected patients who are experiencing refractory cardiac arrest (CA). In the light of increasing availability, the analyses of outcome-relevant predisposing characteristics are of growing importance. We evaluated the prognostic influence of gender in patients presenting with out-of-hospital cardiac arrest (OHCA) treated with eCPR. Methods We retrospectively analysed the data of 377 consecutive patients treated for OHCA using eCPR in our cardiac arrest centre from January 2016 to December 2022. The primary outcome was defined as the survival of patients until they were discharged from the hospital, with a favourable neurological outcome [cerebral performance category (CPC) score of ≤2]. Statistical analyses were performed using baseline comparison, survival analysis, and multivariable analyses. Results Out of the 377 patients included in the study, 69 (21%) were female. Female patients showed a lower prevalence rate of pre-existing coronary artery disease (48% vs. 75%, p < 0.001) and cardiomyopathy (17% vs. 34%, p = 0.01) compared with the male patients, while the mean age and prevalence rate of other cardiovascular risk factors were balanced. The primary reason for CA differed significantly (female: coronary event 45%, pulmonary embolism 23%, cardiogenic shock 17%; male: coronary event 70%, primary arrhythmia 10%, cardiogenic shock 10%; p = 0.001). The prevalence rate of witnessed collapse (97% vs. 86%; p = 0.016) and performance of bystander CPR (94% vs. 85%; p = 0.065) was higher in female patients. The mean time from collapse to the initiation of eCPR did not differ between the two groups (77 ± 39 min vs. 80 ± 37 min; p = 0.61). Overall, female patients showed a higher percentage of neurologically favourable survival (23% vs. 12%; p = 0.027) despite a higher prevalence of procedure-associated bleeding complications (33% vs. 16%, p = 0.002). The multivariable analysis identified a shorter total CPR duration (p = 0.001) and performance of bystander CPR (p = 0.03) to be associated with superior neurological outcomes. The bivariate analysis showed relevant interactions between gender and body mass index (BMI). Conclusion Our analysis suggests a significant survival benefit for female patients who obtain eCPR, possibly driven by a higher prevalence of witnessed collapse and bystander CPR. Interestingly, the impact of patient age and BMI on neurologically favourable outcome was higher in female patients than in male patients, warranting further investigation.